Graphene plasmonics for surface-enhanced infrared spectroscopy - Plyushch, Alexander (2020)
The work, presented in this thesis, focuses on studying graphene as a signal enhancing material for spectroscopic applications. Among many outstanding characteristics of graphene, it also exhibits attractive plasmonic properties. Tunability of the resonance within THz to Mid-IR range and high field confinement factor makes it a great candidate for the surface enhanced infrared spectroscopy application. This thesis presents the results of computational and experimental investigation of graphene-based optical resonators. The numerical study was focused on the optimization of two-dimensional graphene geometries, looking to achieve the highest enhancement factor. The experimental part of the work included the fabrication process optimization and characterization of produced graphene structures.